The UN secretary-general and moral authority : ethics and religion in international leadership - Kille, Kent J. (Book collections on Project MUSE., 2007)
Once described by Trygve Lie as the most impossible job on earth, the position of UN Secretary-General is as frustratingly constrained as it is prestigious. The Secretary-General's ability to influence global affairs often depends on how the international community regards his moral authority. In relation to such moral authority, past office-holders have drawn on their own ethics and religious backgroundsùas diverse as Lutheranism, Catholicism, Buddhism, and Coptic Christianityùto guide the role that they played in addressing the UN's goals in the international arena, such as the maintenance o.